Modified Web Access Pattern (mWAP) Approach for Sequential Pattern Mining - Parmar, Jatin D.; Garg, Sanjay (INFOCOMP Journal of Computer Science, 2007)
With the explosive growth of data available on the World Wide Web, discovery and analysis of useful information from the World Wide Web becomes a practical necessity. Web access pattern, which is the sequence of accesses pursued by users frequently, is a kind of interesting and useful knowledge in practice. Sequential Pattern mining is the process of applying data mining techniques to a sequential database for the purposes of discovering the correlation relationships that exist among an ordered list of events. Web access pattern tree (WAP-tree) mining is a sequential pattern mining technique for web log access sequences, which first stores the original web access sequence database on a prefix tree, similar to the frequent pattern tree (FP-tree) for storing non-sequential data. WAP-tree algorithm then, mines the frequent sequences from the WAP-tree by recursively re-constructing intermediate trees, starting with suffix sequences and ending with prefix sequences. An attempt has been made to modify WAP tree approach for improving efficiency. mWAP totally eliminates the need to engage in numerous reconstruction of intermediate WAP-trees during mining and considerably reduces execution time.